2016
DOI: 10.1038/pr.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic synergism of ocular ketorolac and systemic caffeine citrate in rat oxygen-induced retinopathy

Abstract: Background:Caffeine or ketorolac decrease the risk of retinopathy of prematurity and may act synergistically to improve beneficial effect. Combination of caffeine (Caff) and ketorolac (Keto) to prevent oxygen-induced retinopathy was studied.Methods:Newborn rats exposed to room air (RA) or intermittent hypoxia (IH) consisting of 12% O2 during hyperoxia (50% O2) from birth (P0) had single daily IP injections of Caff from P0-P13 or saline; and/or ocular Keto (Acuvail, 0.45% ophthalmic solution) administered subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…Data from the homogenates were standardized using total cellular protein levels as previously described [29, 3134]. Validation studies comparing serum and plasma VEGF levels show no differences [35].…”
Section: Methodsmentioning
confidence: 99%
“…Data from the homogenates were standardized using total cellular protein levels as previously described [29, 3134]. Validation studies comparing serum and plasma VEGF levels show no differences [35].…”
Section: Methodsmentioning
confidence: 99%
“…This clustering design has been shown to produce severe oxidative stress in neonatal rats [3540]. There were two IH groups corresponding to 7-day (P0-P7), and 14-day (P0-P14).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the safety profile of caffeine (20) and the ability of caffeine to control angiogenic factors, hypoxia‐inducible factor‐1α and VEGF (21, 22), angiogenesis (22, 23) and apoptosis of endothelium cells (24), and other vascular actions (25), this clinical observation raises an exciting possibility that caffeine may protect against pathologic neovascularization in ROP; however, this therapeutic strategy against ROP has not been directly tested. A recent study demonstrated that ocular ketorolac and systemic caffeine individually or synergistically reduced retinal neovascularization in rat oxygen‐induced retinopathy (OIR) (26). Several critical issues, such as the selectivity of caffeine effects on normal retinal vascularization development from pathologic angiogenesis, effective therapeutic window, and the actual molecular pharmacologic targets have not been addressed experimentally.…”
mentioning
confidence: 99%